Pulping of Bauhinia purpurea (Kanchan) - Kumar, Krishan (Indian Forester, 1980)
Proximate chemical analysis and fibre dimensions of Bauhinia purpurea (Kanchan) have been recorded. Pulping of the above wood by sulphate process for wrapping, writing and printing papers is described. Suitability indices as compared to Bamboo are also calculated and it is observed that the species is suitable for making the above grades of paper.